Social support, physical and mental health, and alcohol and tobacco use in cancer patients in the State of Mato Grosso, Brazil (Acta Scientiarum. Health Sciences, 2025)
This study aimed to examine the association between sociodemographic characteristics and extremes of social support in patients with cancer in the state of Mato Grosso. This study compared the levels of social support (high and low) with patients' physical and mental health, as well as their alcohol and/or tobacco use. Method: Cross-sectional study with 765 patients undergoing cancer treatment in Mato Grosso, Brazil, from 2019 to 2021. This study examined sociodemographic data, information about physical and mental health, patterns of alcohol and tobacco use, and social support. Poor social support was defined as having an MOS-SSS score below the 25 percentile for the entire sample. Results: As expected, individuals with a high level of social support exhibited better mental health and reduced alcohol and tobacco use. Conversely, individuals with smaller social networks and no religious affiliation had lower levels of social support and were more prone to depressive symptoms, suicidal thoughts, respiratory diseases, and metastasis. However, patients with a low level of social support had a lower-than-expected level of alcohol/tobacco use. In addition, contrary to previous studies, participants with high social support did not engage in binge drinking to the same extent as expected. Conclusion: Health professionals in oncology services must be aware of mental health problems, particularly substance use, and of the importance of monitoring social support in this population.